Early onset lung cancer, cigarette smoking and the SNP309 of the murine double minute-2 (MDM2) gene: Research article - Mittelstraß, Kirstin; Sauter, Wiebke; Rosenberger, Albert; Illig, Thomas; Timofeeva, Maria; Klopp, Norman; Dienemann, Hendrik; Meese, Eckart; Sybrecht, Gerhard W.; Woelke, Gabi; Cebulla, Mathias; Degen, Maria; et al. (BMC cancer, 2008)
The polymorphism SNP309 (rs2279744) in the promoter region of the MDM2 gene has been shown to alter protein expression and may play a role in the susceptibility to lung cancer. The MDM2 protein is a key inhibitor of p53 and several mechanisms of MDM2/p53 interactions are presently known: modulating DNA-repair, cell-cycle control, cell growth and apoptosis. We used 635 Caucasian patients diagnosed with lung cancer before 51 years of age and 1300 healthy gender and age frequency matched population Caucasian controls to investigate the association between the MDM2 SNP309 and the risk of developing early onset lung cancer. Conditional logistic models were applied to assess the genotype-phenotype association, adjusted for smoking. Compared to the GG genotype, the adjusted ORs for the TG and TT genotype were 0.9 (95% CI: 0.71.5) and 1.0 (95% CI: 0.71.5), respectively. Also no association was found for histological subtypes of lung cancer. The strength of this study is that within young cases the genetic component to develop lung cancer may be greater. Our results indicate that the MDM2 SNP309 is not significantly associated with lung carcinogenesis but point towards gender-specific differences.